Randomized, Controlled, Multicentered, Double-Blind Investigation of Injectable Poly-L-Lactic Acid for Improving Skin Quality. Issue 5 (May 2019) - Bohnert, Krista; Dorizas, Andrew; Lorenc, Paul; Sadick, Neil S.
Abstract : BACKGROUND: Poly-L-lactic acid (PLLA) is an injectable filler used for restoring facial fat volume loss. OBJECTIVE: To evaluate the effect of repeated PLLA injections on skin quality. METHODS: Forty healthy women were enrolled in this randomized, controlled, double-blind, multicenter study. Eligible subjects received 3 treatments every 4 weeks with either PLLA (treatment group) or saline (control group) injections, into both sides of the face. Follow-up visits were at 6, 9, and 12 after the last treatment. Assessments included biophysical measuring instruments, live ratings, patient questionnaires, and rating of standardized pictures by a blinded evaluator. RESULTS: At the 12-month follow-up, there was a statistically significant increase of skin elasticity and hydration in PLLA-treated subjects and a decrease in transepidermal water loss in both groups. Pigmentation, erythema, and pore size were significantly decreased, whereas radiance and smoothness were significantly increased at 12 months per blinded investigator rating in this group. No treatment-related adverse events occurred. CONCLUSION: Repeated PLLA treatments may improve skin quality in a time-dependent manner. Abstract : Supplemental Digital Content is Available in the Text.